2010
DOI: 10.1007/s11368-010-0242-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide emissions from animal urine as affected by season and a nitrification inhibitor dicyandiamide

Abstract: Purpose Nitrous oxide emissions from pasture soils account for one third of total agricultural greenhouse gas emissions in New Zealand. The aim of this study was to determine nitrous oxide (N 2 O) emissions from animal urine patches under summer (with irrigation) and winter conditions as affected by dicyandiamide (DCD) in grazed grassland in New Zealand. Materials and methods Sixteen monolith lysimeters were collected from an established perennial ryegrass (Lolium perenne) and white clover (Trifolium repens) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 24 publications
(30 reference statements)
0
14
0
Order By: Relevance
“…This is in contrast to the findings of Weiske et al ( The mean N 2 O EF for urine applications from the present study was 0.41%, within the range of 0.02-1% reported by Yamulki et al (1998) from measurements on the heaviertextured North Wyke soil, but considerably lower than the IPCC default EF of 2% for cattle excreta, suggesting that the UK should develop country-specific EF for cattle urine and dung for use in the UK greenhouse gas inventory in a similar way to New Zealand which derived values of 1 and 0.25% for cattle urine and dung, respectively (Luo et al 2009). Qiu et al (2010) reported higher EF for winter than summer urine applications (1.27 and 0.78%, respectively) in a study in New Zealand. In the UK, winter grazing generally does not occur so a representative EF should integrate spring, summer and autumn conditions.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 87%
See 1 more Smart Citation
“…This is in contrast to the findings of Weiske et al ( The mean N 2 O EF for urine applications from the present study was 0.41%, within the range of 0.02-1% reported by Yamulki et al (1998) from measurements on the heaviertextured North Wyke soil, but considerably lower than the IPCC default EF of 2% for cattle excreta, suggesting that the UK should develop country-specific EF for cattle urine and dung for use in the UK greenhouse gas inventory in a similar way to New Zealand which derived values of 1 and 0.25% for cattle urine and dung, respectively (Luo et al 2009). Qiu et al (2010) reported higher EF for winter than summer urine applications (1.27 and 0.78%, respectively) in a study in New Zealand. In the UK, winter grazing generally does not occur so a representative EF should integrate spring, summer and autumn conditions.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 87%
“…A more conservative emission reduction factor of 50% was suggested for inclusion in the New Zealand agricultural emission inventory to reflect adoption of this mitigation measure (Clough et al 2007). Qiu et al (2010) showed DCD to be more effective at reducing emissions from urine applications to grassland in New Zealand in the higher-emitting winter season (mean 69% reduction) than in summer (mean 40% reduction). It is known that the microbial degradation of DCD in soil is temperature dependent (Kelliher et al 2008) and maximum nitrification inhibition has been reported to occur at soil temperatures ⩽10°C (Di andCameron 2004, Smith et al 1989).…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 98%
“…As the annual N fertiliser rate is the key input into national inventory Tier 1 and Tier 2 methods (DCCEE 2010a), offset methods that result in net reductions in annual fertiliser rate would be reasonably simple to implement. Likewise, nitrification inhibitors, used as a coating on fertiliser or as a spray, have been well documented for temperate latitudes in Australia (Kelly et al 2008) and New Zealand (Di et al 2009Qiu et al 2010;de Klein et al 2011).…”
Section: Brief Introduction To Policy Settings In Australiamentioning
confidence: 99%
“…; Qiu et al . ). High N 2 O emissions from winter‐grazed pastures are often observed when the soil moisture is near or above field capacity, which is indicative of reduced soil aeration promoting denitrification or nitrifier‐denitrification activity (Balaine et al .…”
Section: Introductionmentioning
confidence: 97%
“…However, in grazed pastures, higher N 2 O emissions may actually occur during the autumn/winter seasons, compared to the emissions in spring/summer seasons (Klein et al 2003;Saggar et al 2004a;de Klein et al 2006;Luo et al 2007;Qiu et al 2010). High N 2 O emissions from winter-grazed pastures are often observed when the soil moisture is near or above field capacity, which is indicative of reduced soil aeration promoting denitrification or nitrifier-denitrification activity Zhu et al 2013).…”
Section: Introductionmentioning
confidence: 99%